Validitas dan Praktikalitas Multimedia Interaktif Berbasis Inkuiri Terbimbing pada Materi Asam Basa untuk Peserta Didik Tingkat SMA/MA - Easy Kurniawati; Syamsi Aini (Jurnal Penelitian Pendidikan IPA, 2022)
This research aims to generate a guided inquiry-based interactive multimedia on an Acid-Based product. It also categorizes its validity and practicality. The method of research used in this paper is research that will create a certain product called Research and Development (R&D). Three phases of the Plomp Model will be used in this research including preliminary research phase, prototyping phase, and assessment phase. In this research, the instrument will be used in a questionnaire consisting of a validity sheet and practicality sheet. The actual product was validated by 6 chemistry expert validators and 3 multimedia expert validators. The practicality test was carried out by 2 chemistry teachers and 33 students of XI MIPA 3 from SMAN 2 Padang Panjang. The data analysis technique used is Aiken’s V technique for validity and the percentage technique for practicality. The result of the analysis of the chemistry expert validation and multimedia expert validation data based on Aiken’s V value showed a result of 0,92 and 0,98 with a valid category. The practicality of interactive multimedia results was 88,33 and 87,60 with a very high practice. The interactive multimedia that has been produced is valid and practical to be used.